Cytoprotection assessment against mycotoxins on HepG2 cells by extracts from Allium sativum L. (May 2021) - Juan-García, Ana; Agahi, Fojan; Drakonaki, Maria; Tedeschi, Paola; Font, Guillermina; Juan, Cristina
Abstract: Cytoprotection effects of Allium sativum L garlic extract from a local garlic ecotype from Ferrara (Italy) on hepatocarcinoma cells, HepG2 cells, is presented in this study. This garlic type is known as Voghiera garlic and has been characterized as PDO (Protected designation of Origin) product. Voghiera garlic extract (VGE) was evaluated against beauvericin (BEA) and two zearalenone (ZEA) metabolites (α-zearalenol (α-ZEL) and β-zearalenol (β-ZEL))-induced cytotoxicity on HepG2 cells by the MTT (3–4, 5-dimethylthiazol-2-yl]-2, 5-diphenyltetrazolium bromide) assay, over 24 h and 48 h. Direct treatment, simultaneous treatment and pre-treatment strategies at the dilution 1:16–1:00 for VGE and at the concentration range from 0.08 to 2.5 μM for BEA and from 1.6 to 50 μM for both α-ZEL and β-ZEL were tested. Individual IC50 values were detected at all times assayed for BEA (>0.75 μM) and VGE (dilution upper 1:8) while this was not observed for ZEA's metabolites. When simultaneous strategy of VGE + mycotoxin was tested, cytoprotection with increases of viability (upper 50%) were observed. Lastly, in pre-treatment strategy with VGE, viability of HepG2 cells was significantly protected when α-ZEL was tested. As a result, the greatest cytoprotective effect of VGE in HepG2 cells is obtained when simultaneous treatment strategy was performed. Highlights: Cytotoxicity of α-ZEL, β-ZEL and BEA on HepG2 cells alleviated by extracts of Allium Sativum L. IC50 values for BEA (>0.75 μM) and Voghiera Garlic Extract (VGE) (upper 1:8) were observed. VGE + mycotoxins in simultaneously strategy exert cytoprotection (upper 50%) on HepG2 cells. Pre-treatment strategy with VGE, protected HepG2 cells when exposed to α-ZEL.